Citizens with Disability – Crisis of the Welfare State in Europe? - Michalík, Jan (Social Welfare: Interdisciplinary Approach, 2011)
The present paper brings a basic characteristic of once in Europe common form of the welfare state, including its currently published criticism. It presents the examples of disintegration of traditional values of social solidarity. It deals with risks that may arise from the potential development and that may threaten citizens with disability who are still predominantly perceived as subjects of social solidarity. In the environment of the European Union it concerns demographic aspects (aging population), increasing expenses on welfare transfers and the development of medicine as the economically most demanding subsystem of public budgets of the future.